Evaluation of Graduate Students Employability from Employer Perspective: Review of the Literature - Ibrahim Gamer Eldeen, Asma; Ali Abumalloh, Rabab; P George, Remya; A Aldossary, Danah (International Journal of Engineering and Technology, 2018)
Graduate employability is a critical issue in Higher Education. Employers are expecting not only the subject knowledge from the students to compete with the current industry demands, but also additional skills to face corporate battles and challenges. The aim of this research is to identify the skills demanded by the employers and to incorporate them in the learning outcomes of higher education. This research aims to review and analyses all the papers published from 2010 until now regarding the evaluation of graduate students from employersâ€™ perspectives. This subject has been rarely touched in literature and needs more focus regarding to its importance for both education institutions and employers. Papers were collected from different databases and carefully analyzed by the authors. Different classification methods were done. The results were analyzed. The results indicate that there is a gap between the learning outcome and the employability skills.Â Â